Identification of Thioredoxin Glutathione Reductase Inhibitors That Kill Cestode and Trematode Parasites - Ross, Fabiana (Public Library of Science, 2012)
Parasitic flatworms are responsible for serious infectious diseases that affect humans as well as livestock animals in vast regions of the world. Yet, the drug armamentarium available for treatment of these infections is limited: praziquantel is the single drug currently available for 200 million people infected with Schistosoma spp. and there is justified concern about emergence of drug resistance. Thioredoxin glutathione reductase (TGR) is an essential core enzyme for redox homeostasis in flatworm parasites. In this work, we searched for flatworm TGR inhibitors testing compounds belonging to various families known to inhibit thioredoxin reductase or TGR and also additional electrophilic compounds. Several furoxans and one thiadiazole potently inhibited TGRs from both classes of parasitic flatworms: cestoda (tapeworms) and trematoda (flukes), while several benzofuroxans and a quinoxaline moderately inhibited TGRs. Remarkably, five active compounds from diverse families possessed a phenylsulfonyl group, strongly suggesting that this moiety is a new pharmacophore. The most active inhibitors were further characterized and displayed slow and nearly irreversible binding to TGR. These compounds efficiently killed Echinococcus granulosus larval worms and Fasciola hepatica newly excysted juveniles in vitro at a 20 µM concentration. Our results support the concept that the redox metabolism of flatworm parasites is precarious and particularly susceptible to destabilization, show that furoxans can be used to target both flukes and tapeworms, and identified phenylsulfonyl as a new drug-hit moiety for both classes of flatworm parasites.